Hydrodynamical moving-mesh simulations of the tidal disruption of stars by supermassive black holes. Issue 1 (17th May 2019) - Goicovic, Felipe G; Springel, Volker; Ohlmann, Sebastian T; Pakmor, Rüdiger
Abstract: When a star approaches a black hole closely, it may be pulled apart by gravitational forces in a tidal disruption event (TDE). The flares produced by TDEs are unique tracers of otherwise quiescent supermassive black holes (SMBHs) located at the centre of most galaxies. In particular, the appearance of such flares and the subsequent decay of the light curve are both sensitive to whether the star is partially or totally destroyed by the tidal field. However, the physics of the disruption and the fallback of the debris are still poorly understood. We are here modelling the hydrodynamical evolution of realistic stars as they approach an SMBH on parabolic orbits, using for the first time the moving-mesh codearepo, which is particularly well adapted to the problem through its combination of quasi-Lagrangian behaviour, low advection errors, and high accuracy typical of mesh-based techniques. We examine a suite of simulations with different impact parameters, allowing us to determine the critical distance at which the star is totally disrupted, the energy distribution and the fallback rate of the debris, as well as the hydrodynamical evolution of the stellar remnant in the case of a partial disruption. Interestingly, we find that the internal evolution of the remnant's core is strongly influenced by persistent vortices excited in the tidal interaction. These should be sites of strong magnetic field amplification, and the associated mixing may profoundly alter the subsequent evolution of the tidally pruned star.